Effect of supplement strategy on intake and digestion of prairie hay by beef steers - R.H. Greenwood; C.A. Loest; Evan C. Titgemeyer; James S. Drouillard (Kansas Agricultural Experiment Station Research Reports, 1997)
The effects of supple mental corn (4 lb/day), rumen-protected methionine (4.25 grams DL-methionine per day), or a cooked molasses block (1 lb/day) on intake and digestion of prairie hay were measured i n beef steers. Steers that consumed the cooked molasses block ate more forage than control steers, whereas forage intake was decreased by supplemental corn. Total tract organic matter digestion, expressed as a percent of intake, was numerically greatest for steers consuming the cooked molasses block. Digestible organic matter intake, a rough estimate of energy available to the steers, was unaffected by methionine but was increased by supplementation of either corn or the cooked molasses block. Digestible organic matter intake tended to be greater for the block than for corn. Providing protein in a more concentrated form (block) tended to be more beneficial, because the negative effects of starch (corn) on forage intake were avoided.
Keywords: Cattlemen' s Day; 1997; Kansas Agricultural Experiment Station contribution; no. 97-309-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 783; Beef; Steers; Forage; Intake; Digestibility